Minority Status and Labor Market Outcomes : Does India Have Minority Enclaves? - Das, Maitreyi Bordia (World Bank, Washington, DC, 2012)
This paper uses data from the 61st Round of the National Sample Survey to understand the employment outcomes of Dalit and Muslim men in India. It uses a conceptual framework developed for the US labor market that states that ethnic minorities skirt discrimination in the primary labor market to build successful self-employed ventures in the form of ethnic enclaves or ethnic labor markets. The paper uses entry into self-employment for educated minority groups as a proxy for minority enclaves. Based on multinomial logistic regression, the analysis finds that the minority enclave hypothesis does not hold for Dalits but it does overwhelmingly for Muslims. The interaction of Dalit and Muslim status with post-primary education in urban areas demonstrates that post-primary education confers almost a disadvantage for minority men: it does not seem to affect their allocation either to salaried work or to non-farm self-employment but does increase their likelihood of opting out of the labor force - and if they cannot afford to drop out, they join the casual labor market. Due to the complexity of these results and the fact that there are no earnings data for self-employment, it is difficult to say whether self-employment is a choice or compulsion and whether builders of minority enclaves fare better than those in the primary market.